2015
DOI: 10.1107/s2053230x15015290
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and initial crystallographic analysis of covalent DNA-cleavage complexes of Staphyloccocus aureus DNA gyrase with QPT-1, moxifloxacin and etoposide

Abstract: Fluoroquinolone drugs such as moxifloxacin kill bacteria by stabilizing the normally transient double-stranded DNA breaks created by bacterial type IIA topoisomerases. Previous crystal structures of Staphylococcus aureus DNA gyrase with asymmetric DNAs have had static disorder (with the DNA duplex observed in two orientations related by the pseudo-twofold axis of the complex). Here, 20-base-pair DNA homoduplexes were used to obtain crystals of covalent DNA-cleavage complexes of S. aureus DNA gyrase. Crystals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…As part of a structure-based approach to develop novel bacterial topo2A pharmacophores, we co-crystallized and determined structures 22 of DNA-cleavage complexes of the S. aureus B27-A56(GKdel) fusion truncate (gyrase CORE ) with QPT-1, etoposide and moxifloxacin ( Figs 1 , 2 , 3 , Table 1 , Supplementary Fig. 2 and Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of a structure-based approach to develop novel bacterial topo2A pharmacophores, we co-crystallized and determined structures 22 of DNA-cleavage complexes of the S. aureus B27-A56(GKdel) fusion truncate (gyrase CORE ) with QPT-1, etoposide and moxifloxacin ( Figs 1 , 2 , 3 , Table 1 , Supplementary Fig. 2 and Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 ). These complexes (ba_ba' 2–QPT , BA_BA' 2–QPT and BA_BA' 2 − QPT ; see Table 1 ) come from the 2.5- and 3.15-Å QPT-1 co-crystal structures, which were obtained under the same crystallization conditions 22 . When the QPT-1-binding sites are compared ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel with the biochemical and genetic studies, we explored cocrystallization of the inhibitor with DNA gyrase. We have found that the S. aureus DNA gyrase crystallography platform can be used to gain structural information on compounds that target both Grampositive and Gram-negative organisms (15,19,24). Using this crystallographic platform, we obtained a 1.98-Å structure of compound 1 complexed to an S. aureus DNA gyrase core fusion [lacking the gyrase A (GyrA) C-terminal domain, the gyrase B (GyrB) Greek-key domain, and the GyrB N-terminal domain] and DNA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins were purified and complexes were prepared and crystallized and structures were determined using methods as previously described (19,24). The X-ray data collection (35) and refinement statistics for the two thiophene structures described in this paper are shown in SI Appendix, Table S1.…”
Section: Methodsmentioning
confidence: 99%